Towards modelling the formation of ore bodies initial results dealing with the fluid mechanical aspects of magma chamber convection - Botha, André Erasmus (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1999)
This thesis forms part of a larger effort which aims to establish the means of assessing the fluid mechanical behaviour of magma 1 as it cools inside a magma chamber surrounded by porous country rock. The reason for doing so is to advance the understanding of some types of mineral deposits; for example,the Platinum Group Elements (PGEs). The magma is modelled with the governing equations for a single-phase incompressible Newtonian fluid with variable viscosity and density. In this thesis, thermal conductivity and specific heat are approximated as constants and the country rock is treated as a conducting solid so as to save on computational time in the initial phases of the project. A basic review of the relevant literature is presented as background material and three basic models of magma chambers are discussed: crystal settling, compositional convection and double diffusive convection.The results presented in this thesis are from finite element calculations by a commercial computer code: ANSYS 5.4. This code has been employed in industry for over 26 years and has a long and successful benchmark history. In this context, finite element methods that are applicable to the code are discussed in chapter 5. In chapter 6, results that were obtained in the course of this research are presented. The thesis concludes with an indication of the possible geological significance of the results and various refinements that should be made to future models.
Keywords: Ore deposits; Fluid mechanics; Magmatism